An equvilent equation
remember you can do anything to an equation as long asyou do it to both sides
assuming yo have
x+y=1 and
x-3y=9
mulitply both by 2
2x+2y=2
2x-6y=18
those are equvilent
ok, solve initial
x+y=1
x-3y=9
multiply first equation by -1 and add to 2nd equation
-x-y=-1
<u>x-3y=9 +</u>
0x-4y=8
-4y=8
divide both sides by -4
y=-2
sub back
x+y=1
x-2=1
add 2
x=3
x=3
y=-2
(3,-2)
if we test it in other one
2x+2y=2
2(3)+2(-2)=2
6-4=2
2=2
yep
2x-6y=18
2(3)-6(-2)=18
6+12=18
18=18
yep
solution is (3,-2)
Answer:
1) 20.9
2) 896
3) 21
Step-by-step explanation:
1) 5.6÷2^3+(12.75+7.45)
---> 12.75 + 7.45 = 20.2
÷
--> Simplify 2^3 to 8
÷ 8 + 20.2
--> 5.6 ÷ 8 = 0.7
--> Simplify
2) 4^3 × (0.6 +3.6) ÷ 0.3
---> 0.6 + 3.6 = 4.2
4^3 * 4.2 ÷ 0.3
---> 4^3 = 64
64 * 4.2 ÷ 0.3
--> 64 * 4.2 = 268.8
268.8 ÷ 0.3
--> 268.8 ÷ 0.3 = 896
896
3) 2^4 + (2.75 +1.75) ÷ 0.9
--> 2.75 + 1.75 = 4.5
2^4 + 4.5 ÷ 0.9
--> 2^4 = 16
16 + 4.5 ÷ 0.9
--> 4.5 ÷ 0.89 = 5
16 + 5
--> Simplify
= 21
Your answers we equal to 22
Answer:
fifteen seconds after that one of my friend did a few days wale and then a
Do you mean the phythagorus theorum: a squared + b squared= c squared